The Effectiveness of Online and Offline Learning: Comparative Study at English Education Department University of Mataram - Putri, Nanda Damayanti; Amin, Muhammad; Putera, Lalu Jaswadi; Susanti, Ni Wayan Mira (Journal of English Education Forum (JEEF), 2024)
This thesis aims to find the effective implementations between online and offline learning and determine which learning mode is effective at the University of Mataram. This study focused on comparing the effectiveness of different modes of learning implementations based on students’ perceptions. The subject of this study is the students at the English Education Department University of Mataram who had experience with online, offline, and blended learning in the class. The researcher analyzes data using mixed methods (qualitative and quantitative) according to Sugiyono (2017). In this thesis researcher chose the sixth semester, that frequently used between online and offline learning with five classes, and chose one class to observe consisting of 27 students, the researchers collected the data using two different instruments, there are questionnaires researcher collected data related to the effectiveness of online and offline learning using a closed-ended questionnaire and the second one is an interview that’s researcher interviewed some students to know about students' perceptions of online and offline learning in the class. The result that the researcher compared was that offline learning was perceived to be a more effective learning mode this is shown by the higher agreement percentage in key aspects such as syllabus (58.3%), teaching method (44.4%), and discussion (48.1%). Moreover, the implementation of offline and online learning has various aspects in the learning process that can help a teacher and researcher in the future explore more pedagogical strategies and instruction design principles that promote effective offline and online learning experiences.